IMPACTS OF CLIMATE CHANGE ON TOURISM IN THE PROVINCES ALONG THE MEKONG RIVER IN THAILAND - Sakkarin NONTHAPOT; Tanawat WATCHALAANUN (Geo Journal of Tourism and Geosites)
The objective of this study was to consider the impacts of climate change on tourism along the Mekong River in Thailand. The factors to be considered included temperature and rainfall on the number of Thai and international tourists. Panel data were used, i.e., cross-sectional data from eight provinces of Thailand located along the Mekong River, from January 2013 to December 2023. The results revealed that, over the long-term, only higher temperatures affected the number of Thai tourists. In the short run, average temperatures and rainfall showed the opposite relationship with regard to the number of Thai tourists. The results identified climate change as a cause of the smaller number of Thai tourists in those provinces, mainly as a resul t of higher average temperatures. Therefore, higher temperatures could be considered a major obstacle for tourism activities.